Feasibility of Digital Comic Media in Enhancing Early Reading Skills for First-Grade Elementary School Students - Vadila Nurista Ananda; Kadek Yudiana; Putu Rahayu Ujianti (Universitas Pendidikan Ganesha, 2024)
Not all new students are able to understand letters or reading materials effectively. Many first-grade elementary school students still face challenges in learning to read. This study aims to develop a digital comic learning media designed to improve the reading skills of first-grade elementary school students, particularly on the topic of